2022
DOI: 10.1186/s12969-022-00733-3
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine versus cimetidine: the better choice for Periodic fever, aphthous stomatitis, pharyngitis, adenitis (PFAPA) syndrome prophylaxis, and the role of MEFV gene mutations

Abstract: Background During childhood, the most common periodic fever is periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome. The effective treatment and prevention of febrile attacks improve these patients' and their families’ quality of life. However, there is no single strategy or evidence-based guideline to manage this syndrome, and most of them are based on consensus treatment plans. Methods This randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Due to its efficacy in patients with FMF, it has been studied in PFAPA as well [31][32][33]. Additional studies over the past two years showed that colchicine reduces the frequency of flares in children with PFAPA [25,26,34,35]. In one of these, 67 Iranian children were randomly assigned to either prophylaxis with colchicine or cimetidine; both of these prophylactic agents were found to have similar efficacy [35].…”
Section: New Data On Treatment Strategiesmentioning
confidence: 99%
“…Due to its efficacy in patients with FMF, it has been studied in PFAPA as well [31][32][33]. Additional studies over the past two years showed that colchicine reduces the frequency of flares in children with PFAPA [25,26,34,35]. In one of these, 67 Iranian children were randomly assigned to either prophylaxis with colchicine or cimetidine; both of these prophylactic agents were found to have similar efficacy [35].…”
Section: New Data On Treatment Strategiesmentioning
confidence: 99%
“…Several studies with small patient cohorts have found that cimetidine, a histamine- 2 (H 2 ) receptor antagonist, shows some preventive effect in 27% to 44% of patients, though that means that more than half of patients are not responsive 5,12. Evidence supporting use of cimetidine is insufficient, but studies are ongoing 24,25…”
Section: Treatmentmentioning
confidence: 99%
“…5,12 Evidence supporting use of cimetidine is insufficient, but studies are ongoing. 24,25 Colchicine, an anti-inflammatory medication most commonly used to treat gout, is showing some promise as a preventive agent for PFAPA. 5 Because it is used as the treatment of choice in FMF, colchicine was trialed for PFAPA, given the two disordersÕ somewhat similar inflammatory pathways.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Treatment of the syndrome is usually symptomatic with a single low-dose betamethasone (0.1 mg/kg) or prednisone (1 mg/kg), being the most effective option to abort acute disease flares ( 8 ). Colchicine has also been proven to be effective in preventing PFAPA flares ( 9 ). Different reports have also revealed that tonsillectomy may provide symptom resolution in PFAPA syndrome, though the disease might reoccur later, at least in a minority of patients ( 10 ).…”
Section: Introductionmentioning
confidence: 99%